PENILAIAN DAN AKUNTANSI GOODWILL - Aji Suryo (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2008)
Accounting for acquisition consists of decisions on cost of acquisition, allocation process for assets and liabilities for acquiring and accounting of goodwill that arise from the acquiring company. The matters that can be arise from business combination consists of decision of minority factors, accounting for recording several periods, the changes of cost, the identify of assets and liabilities and other disclosures. SFAS 142, Goodwill and other intangible assets give some new conceptual reports for business valuation. The implementation of SFAS 142 has been stated at SFAS 141, business combination. Because of SFAS 142, the accountant and finance professional that follow this standard should know about several principles, methods, and techniques on business valuation. With the changes of acquisition technique, it does not mean that the investor expectation will be changes too. Accounting for goodwill has a close relationship with the excess earning of par; include in the investor interest of excess earning of par and increasing the values of company. The relationship will affect the investor act more carefully and due care about the changes of the values than the role of accounting itself. To anticipate the values and investor’s expectation, investor can implement the framework of economic value added (EVA).Keywords: acquisition, goodwill, business combination, intangible assts and economic value added.